Geometrization of ferruginous quartzite massifs based on geological and structural mapping results and improvement of deposit GIM (the case of Skelyuvatsk deposit) - Стеценко, Вячеслав Валерійович; Осипчук, Вікторія Юріївна (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
The purpose of the paper is to develop generalized methods of ferruginous quartzite massifs geometrization based on the results of geological and structural mapping. The main objective is to improve the geological and industrial model (GIM) of the fields in Kryvbas region on the whole and Skelyuvatsk deposit in part.For methodology development of ferruginous quartzite massifs geometrization GIM Skelyuvatsk deposit has been developed based on the results of geological and structural mapping and the comparative analysis of the existing GIM used at the enterprise has been carried out.The comparative analysis has showed that GIM developed on the basis of the geological and structural mapping data is more advanced and informative. The use of geological and structural data for the development of GIM reduces the relative error in the calculation of ore reserves, increases the effectiveness of geometrization of ferruginous quartzite massifs and demonstrates geological structure of the region with the simulation of the productive layer boundaries, contacts of rocks and the internal structure of Skelyuvatsk deposit.Scientific novelty is in the development of the new GIM of Skelyuvatsk deposit with consideration of geological and structural mapping data.Practical relevance of the research. The use of the obtained GIM on the basis of the geological and structural mapping data increases the efficiency of geological profile forecast and the information required for finding the solution to stability of an open-pit sides within a final pit boundary and rational arrangement of drill holes in a large-scale blast plan during the development of open-pit benches in a designed position.